Exploration of hydrocarbon traps using two methods within the Bogatoika area of the Dnieper-Donetsk Depression ― comparison of geological results - О.М. Шадура (Геофизический журнал, 2025)
The paper aims to show the efficiency of a novel estimation technique for oil and gas in reservoirs in complicate-constructed (non-anticline) traps. In contrast to traditional techniques, which require tracing two horizons to estimate a complicated trap, this one uses only one horizon that crosses the reservoir.